Bridging the Integration Deficit: Developing an Integrated Psychosocial-Financial Health Model for Buy Now, Pay Later Adoption - Ashri Putri Rahadi (Research Synergy Foundation, 2026)
The rapid expansion of Buy Now, Pay Later (BNPL) services has transformed digital finance, yet current scholarship remains siloed in its evaluation of consumer behavior. This systematic literature review addresses the